The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2177-6709.22.4.041-046.oar
|View full text |Cite
|
Sign up to set email alerts
|

Facial profile esthetics in operated children with bilateral cleft lip and palate

Abstract: Objective: The aim of this study was to evaluate the facial profile esthetics of rehabilitated children with complete bilateral cleft lip and palate (BCLP), comparing the judgment of professionals related and not related to cleft rehabilitation and laypersons. Methods:Thirty children in the mixed dentition (24 male; 6 female) with a mean age of 7.8 years were evaluated using facial profile photographs by 25 examiners: 5 orthodontists and 5 plastic surgeons with experience in cleft care, 5 orthodontists and 5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Lauris et al evaluated the esthetics of the facial profile of children rehabilitated with CLP, comparing the judgment of professionals related and unrelated to the rehabilitation of clefts and laypeople, and the results revealed that professionals related to cleft rehabilitation were kinder and those unrelated to cleft treatment were stricter about facial esthetics than laypeople. [12] In the studies by Alhayek et al and the professionals were more satisfied than laypeople, corroborating that there are differences in perception between health professionals and laypeople, and the discrepancies between professional groups can be attributed to different treatment modalities and protocols. [13,14] According to Papamanou et al (2012), this can be explained as a result of the education and experience of specialists, which can lead to an assessment of facial From the perspective of parents and patients, low satisfaction with esthetics was correlated with the increase in self-reported influence of the cleft on the social activity and professional life of patients, as well as their high expectations with the results.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Lauris et al evaluated the esthetics of the facial profile of children rehabilitated with CLP, comparing the judgment of professionals related and unrelated to the rehabilitation of clefts and laypeople, and the results revealed that professionals related to cleft rehabilitation were kinder and those unrelated to cleft treatment were stricter about facial esthetics than laypeople. [12] In the studies by Alhayek et al and the professionals were more satisfied than laypeople, corroborating that there are differences in perception between health professionals and laypeople, and the discrepancies between professional groups can be attributed to different treatment modalities and protocols. [13,14] According to Papamanou et al (2012), this can be explained as a result of the education and experience of specialists, which can lead to an assessment of facial From the perspective of parents and patients, low satisfaction with esthetics was correlated with the increase in self-reported influence of the cleft on the social activity and professional life of patients, as well as their high expectations with the results.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Absence of the lateral incisor is often associated with cleft lip and palate, and the orthodontist along with the rehabilitation team should define the best treatment option in this region. 1,2,[4][5][6]18 Even after a successful secondary graft in the cleft region, there is a tendency to remain a vertical defect in this region, which in most situations contraindicates rehabilitation through implant and prosthesis. 2,5,19 In addition, implant and prosthesis rehabilitation in the long term tends to have a greater aesthetic compromise due to non-vertical physiological migration of the implant, which would imply the need for a new rehabilitation to original article Souza RM, Oliveira HT, Farret MM restore vertical symmetry in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the multifactorial nature of facial attractiveness, its assessment is a complex task and cannot be quantified by a simple measurement. Complete BCLP represents the most severe subtype of oral clefts and accounts for 14% of all types of oral clefts (Lauris et al, 2017). Bilateral CLP causes serious esthetical, functional, anatomic, and psychosocial disorders, a substantial challenge for its surgical and clinical management (Lauris et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Complete BCLP represents the most severe subtype of oral clefts and accounts for 14% of all types of oral clefts (Lauris et al, 2017). Bilateral CLP causes serious esthetical, functional, anatomic, and psychosocial disorders, a substantial challenge for its surgical and clinical management (Lauris et al, 2017). Several studies have evaluated soft tissue morphology in patients with CLP.…”
Section: Discussionmentioning
confidence: 99%